Hiphop in Brussel: eindelijk uit het getto? - Benoit Quittelier (Brussels Studies, 2015)
This article deals with the socio-spatial situation of Hip-Hop. The study of the spatiality of breakdance battles and training illustrates the contemporary transformations which affect the practices related to this culture. With a growing maturity and the evolution of the social basis of these dancers, breakdance has left the ghetto, literally and figuratively. It takes place currently outside the most disadvantaged areas of the city, in the most mixed neighbourhoods at ethnic and socioeconomic level. Breakdance continues to face great difficulties entering the traditional cultural circuits. Daily artistic activities are in a delicate situation, as the organisation of training depends almost entirely on the initiative of the dancers themselves, who must often develop strategies to set up informal places for their activities. However, this type of appropriation of the public or semi-public space does not take place smoothly. The ignorance with respect to hip-hop culture and its relatively bad image, combined with the dancers’ status as vulnerable users in the places they frequent, generate risks of eviction. Less appealing places which are deserted at certain hours – typically railway stations or underground stations – are used more and more.